Supercritical Water Oxidation for Toxic Organic Wastewater Disposal - Bambang Veriansyah; Benedictus Prabowo; Jae-Duck Kim (ASEAN Journal of Chemical Engineering, 2006)
The destruction of toxic organic wastewaters from munitions demilitarization and complex industrial chemicals clearly becomes an overwhelming problem if left to conventional treatment processes. Two options, incineration and supercritical water oxidation (SCWO), exist for the complete destruction of toxic organic wastewaters. Incinerator, on the one hand, has associated problems such as very high cost and public resentment; SCWO, on the other hand, has proven to be a very promising method for the treatment of various types of wastewaters with its extremely efficient organic waste destruction of 99.99% with none of the emissions associated with incineration. In this review, the concepts of SCWO, the results of and present perspectives on its applications, as well as the industrial status of SCWO are critically examined and discussed.